This research is intended to find an accurate of data whether the existence of the Goyor sarong center as a creative economy can create a tourism village with local wisdom for the preservation of Indonesian local culture. This research was conducted at th - dwi irma handayani; Auliyatussaa'adah, Nur; farekha (Journal Of Islamic Economics And Finance, 2021)
The purpose of this study is to determine partially and simultaneouslybetween Islamic stocks and Islamic mutual funds on economicgrowth. The population in this study is Islamic stocks and Islamicmutual funds in the Financial Services Authority data and the value ofIndonesia's GDP at the Central Statistics Agency. While the sample isquarterly report data on Islamic stocks with indicators of ISSI, Islamicmutual funds and economic growth through the value of GDP in theCentral Statistics Agency data for 7 years from 2013 to 2019. Dataanalysis using multiple linear regression analysis. There are severalconclusions from this study: (1) Sharia stocks have a significant effecton Indonesia's economic growth in 2013-2019, (2) Islamic mutualfunds have a significant effect on Indonesia's growth in 2013-2019,(3) Sharia stocks and Islamic mutual funds together had a significanteffect on Indonesia's economic growth in 2013-2019.